Are wildfires a threat for Globose Cacti in the Córdoba mountains, central Argentina? - Gurvich, Diego Ezequiel (2015)
Wildfires are considered a natural disturbance in many ecosystems, but in recent times, worldwide human activities have increased their frequency affecting negatively the vegetation worldwide. In both North and South America, cactus species inhabit mainly arid and semiarid environments, ecosystems that are prone to wildfires. Currently there have been very few studies that have assessed fire effects on cactus species, and those that exist were performed mainly in the northern hemisphere (Thomas 1991).